Literasi Keuangan Syariah pada UMKM dan Dampaknya terhadap Penggunaan Produk Bank Syariah - Mubarok El Alimi (ITB AAS INDONESIA Surakarta, 2023)
In this study, in analyzing the influence of Islamic financial literacy on the variables that were tested, namely the variables of knowledge, skills, and beliefs that were tested partially or simultaneously on the decision to use products in Islamic banks. The data used in this research is primary data by distributing questionnaires to 32 respondents. in this study using the sampling method that is saturated sample. The type in this study is quantitative with multiple linear regression data analysis methods which later from the data obtained will be described. The results of the study show that the level of knowledge, skills and beliefs has an influence on the decision to use Islamic bank products. The coefficient of determination (R2) is 95.3%, which means that the independent variable, namely Islamic financial literacy consisting of knowledge (X1), skills (X2), and confidence (X3) has an effect of 95.3% on the decision to use products in Islamic banks Keywords: Knowledge, Skills, Confidence, Islamic financial literacy, use of Islamic bank products.